2020
DOI: 10.1001/jamanetworkopen.2020.22398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acetaminophen (Paracetamol) With Ibuprofen for Treatment of Fever or Pain in Children Younger Than 2 Years

Abstract: Key Points Question Are there differences in the antipyretic, analgesic, and safety profiles of acetaminophen (paracetamol) compared with ibuprofen for the short-term treatment of fever or pain in children younger than 2 years? Findings In this meta-analysis of 19 studies with 241 138 participants, ibuprofen, compared with acetaminophen, was associated with reduced temperature at less than 4 hours and 4 to 24 hours and less pain at 4 to 24 hours. Adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 56 publications
(280 reference statements)
1
48
0
1
Order By: Relevance
“…and focused on children under 2 years old [11]. Moreover, six related RCTs on this topic had been published before the previous systematic reviews [12][13][14][15][16][17].…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…and focused on children under 2 years old [11]. Moreover, six related RCTs on this topic had been published before the previous systematic reviews [12][13][14][15][16][17].…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…None of the included reviews, barring Cheelo et al, 16 conducted a sensitivity analysis for this. Systematic reviews of RCTs comparing the asthma incidence in children with postnatal exposure to paracetamol or ibuprofen have not found any difference between the two, again supporting confounding by indication 60,61 . One RCT comparing prenatal paracetamol and ibuprofen exposure, enrolling children above 2 months of age, with a 6‐year follow‐up is currently underway 62 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings previously reported by various authors. Southey et al, 2009, and Tan et al, 2020, showed that ibuprofen and acetaminophen have similar safety profiles in pediatric patients [ 47 , 48 ]. van Walsem et al, 2015, found that the risk of fatal and nonfatal severe events was similar between diclofenac, acetaminophen, naproxen, ibuprofen, celecoxib, and etoricoxib.…”
Section: Discussionmentioning
confidence: 99%